The influence of neighbourhood equity on parkrunners in a British city. (6th September 2021) - Haake, Steve; Heller, Ben; Schneider, Paul; Smith, Rob; Green, Geoff
Summary: Physical activity benefits both physical and mental health. Specific events may augment participation in physical activity at a population level. Parkrun is a popular, free, weekly, timed 5 km run or walk in public spaces located in five continents. However, these events may be distributed inequitably, possibly reinforcing inequities in health. As a prelude to a comprehensive analysis of a larger dataset, we explore a hypothesis that participation in parkrun is influenced by the socio-economic characteristics of both parkrunners and their park. Two parkruns, 4.5 km apart, were selected in the city of Sheffield in the United Kingdom. Defined by indices of multiple deprivation, Castle parkrun is located in an economically deprived neighbourhood and Hallam parkrun is in a prosperous area of the city. Parkrunners were defined by applying these same indices to the neighbourhood of home registration. Results: (i) the prosperous Hallam catchment area produced over five times more parkrun participants than Castle; (ii) compared with Castle, Hallam parkrun attracted more participants from both catchment areas; (iii) consequently, Hallam parkrun had seven times more participants than Castle parkrun. Conclusion: establishing parkruns in deprived areas is a necessary but not sufficient prerequisite for equity of participation in this heath promoting activity. Lay Summary: Parkruns are popular, free, weekly, timed 5 km runs or walks in public places across the world. They contribute to both mental and physical health. But they could also increase health inequality. Participants may already have the better health generally associated with above average incomes and home life in attractive neighbourhoods. Our pilot study compares two parkruns in the British city of Sheffield; one located in the city's poorer East End, the other in the richer West End.